Pengembangan Media Video Animasi Pop Up Book Berbasis Budaya Lokal Papua Barat Untuk Meningkatkan Pengetahuan Umum Literasi Budaya Siswa Kelas IV Sekolah Dasar - Nova Nugrahaeni; Yatim Riyanto; Hendratno (Cetta: Jurnal Ilmu Pendidikan, 2023)
Many students, both native Papuans and immigrants, currently do not know their own culture. In addition, through surveys and comparative studies of local culture-based books and media that review the culture in Southwest Papua itself, it is still very rare to find. This study aims to produce the development of an animated video media pop up book based on the local culture of West Papua to increase the general knowledge of cultural literacy of fourth grade elementary school students that is valid, practical, and effective. The research method used is Research & Development to create Pop Up Book Video Animation media. This research utilizes the 4D model for media development. The four steps of the 4D model according to Thiagarajan include: 1) Define which aims to establish learning criteria, such as learning objectives and material limitations; 2) Design aims to design the developed media; 3) Develop, the learning tool underwent the last revision before being published, with adjustments made in response to suggestions from experts and data from trials; 4) Disseminate, students take advantage of learning media that have undergone development and testing on a larger scale, then the product will be disseminated via YouTube. The location of this research was SD Inpres 15 located in Sorong Regency with 5 students selected to take part in small-scale and large-scale trials. The results of the study found that learning using the animated pop up book video media that had been developed could improve student learning outcomes. This can be seen from the number of students who received a complete score on the local culture of Southwest Papua.